Investigating The Engine Propeller Matching Of Triple Screw Ro-Ro Passenger Ship - Bagas Rahkmad Ramadhan; Syafiuddin; Agung Purwana (Surabaya State Polytechnic of Shipbuilding, 2024)
The conversion of a Ro-Ro Vehicle Carrier into a Ro-Ro Passenger Ship. in compliance with PERMEN RI Number PM 62 of 2019. necessitates the use of at least two main engines. This study evaluates the performance of the C5-75 and MAU4-65 propellers to assess their efficiency. At a speed of 21 knots. the C5-75 propeller achieves an efficiency (ŋ) of 0.66 in clean hull conditions and 0.655 in rough hull conditions. The MAU4-65 propeller shows an efficiency of 0.646 in clean hull conditions and 0.653 in rough hull conditions. The Engine Propeller Matching (EPM) only a 12640 kW main engine indicates optimal operation at 109 rpm (clean hull) and 112 rpm (rough hull). Added 2 auxiliary main engine 1040 kW engines operate at 1577 rpm (clean hull) and 1597 rpm (rough hull). These findings highlight the propeller's performance and the required engine settings to achieve the desired speed after conversion.